Does Microfinance Empower Women? Evidence from Self Help Groups in India - Ranjula Bali Swain; Fan Yang Wallentin (Uppsala University, Department of Economics, 2007)
Microfinance programs like the Self Help Bank Linkage Program in India have been increasingly promoted for their positive economic impact and the belief that they empower women. However, only a few studies rigorously examine the link between microfinance and womens empowerment. This paper contributes by arguing that women empowerment takes place when women challenge the existing social norms and culture, to effectively improve their well being. It empirically validates this hypothesis by using quasi-experimental household sample data collected for five states in India for 2000 and 2003. A general structural model is estimated by employing appropriate techniques to treat the ordinal variables in order to estimate the impact of the Self Help Group (SHG) on women empowerment for 2000 and 2003. The results strongly demonstrate that on average, there is a significant increase in the women empowerment of the SHG members group. No such significant change is observed however, for the members of the control group. The elegance of the result lies in the fact that the group of SHG participants show clear evidence of a significant and higher empowerment, while allowing for the possibility that some members might have been more empowered than others.
urn:nbn:se:uu:diva-11479
Keywords: C33; G21; J16; 330; Microfinance; Women empowerment; Ordinal variables; General structural model and Robust maximum likelihood estimation.; Mikrofinanzierung; Frauen; Selbsthilfe; Soziale Norm; Maximum-Likelihood-Methode; Indien